Graduate tracer study: A report on a survey of graduates in engineering (UWI) - National Institute of Higher Education, Research, Science and Technology (NIHERST, 1989)
This preliminary analysis of engineering graduates is part of the first phase of an exercise to develop an estimate of the scientific and technological manpower resources available in Trinidad and Tobago
Keywords: Followup studies